Humidity and CO2 gas sensing properties of double-layer graphene. (February 2018) - Fan, Xuge; Elgammal, Karim; Smith, Anderson D.; Östling, Mikael; Delin, Anna; Lemme, Max C.; Niklaus, Frank
Abstract: Graphene has interesting gas sensing properties with strong responses of the graphene resistance when exposed to gases. However, the resistance response of double-layer graphene when exposed to humidity and gasses has not yet been characterized and understood. In this paper we study the resistance response of double-layer graphene when exposed to humidity and CO2, respectively. The measured response and recovery times of the graphene resistance to humidity are on the order of several hundred milliseconds. For relative humidity levels of less than ∼3% RH, the resistance of double-layer graphene is not significantly influenced by the humidity variation. We use such a low humidity atmosphere to investigate the resistance response of double-layer graphene that is exposed to pure CO2 gas, showing a consistent response and recovery behaviour. The resistance of the double-layer graphene decreases linearly with increase of the concentration of pure CO2 gas. Density functional theory simulations indicate that double-layer graphene has a weaker gas response compared to single-layer graphene, which is in agreement with our experimental data. Our investigations contribute to improved understanding of the humidity and CO2 gas sensing properties of double-layer graphene which is important for realizing viable graphene-based gas sensors in the future. Graphical abstract: Image 1